Importance of tissue culture in propagation of orchids - a review. - Alang, Zaleha Christine (1975)

(untitled)
This papers presents a brief review of the various methods used in the propagation of orchids. It covers the trsditionsl method of vegetative propagation, the development of methods for meristem culture and its impact on the orchid industry.